An interesting case of peripheral arterial disease as presentation in systemic lupus erythematosus - Sumati Kulkarni; Sangram Biradar (Wolters Kluwer Medknow Publications, 2023)
Systemic lupus erythematosus (SLE) is a chronic multisystemic autoimmune disease. Among the cutaneous manifestations of SLE, peripheral arterial disease and digital gangrene are considered very rare. Digital ulcers are relatively rare in SLE and never present as an initial manifestation of disease. The presence of an extremity ulcer is one of the more obvious clinical signs that can be due to ischemia (peripheral arterial disease). Digital gangrene is seen mostly at a late stage of the disease proposing that a long history of SLE is a considered risk factor. Only 0.2% of patients with SLE presented initially as digital necrosis. This is a case report of a 55-year-old male patient who presented with primarily with acute painful localized dry digital gangrene associated with bilateral lower limbs. Serology was positive for SLE. Doppler study of both the lower limbs vessels showed digital artery of second toe of both feet shows reduced flow on doppler study. Disarticulation of the toes was adviced as treatment.